RHYTHMIC AUDITORY STIMULATION TERHADAP PENINGKATAN KECEPATAN BERJALAN PADA PASIEN LANSIA PASCA STROKE - Hansun, Ephyfano; Eman, Friets; Mamuaja, Filly (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2026)
Introduction: Post-stroke is a neurological condition that can cause motor impairments, muscle weakness, coordination disorders, and decreased walking ability. In elderly post-stroke patients, impaired walking speed is one of the most common functional problems that may affect daily activities. Rhythmic Auditory Stimulation (RAS) is a physiotherapy intervention that uses rhythmic auditory cues to help improve gait pattern and walking speed in patients. Objective: To determine the effectiveness of Rhythmic Auditory Stimulation in improving walking speed in elderly post-stroke patients. Methods: This study used a case study method on an elderly post-stroke patient who experienced decreased walking speed. Physiotherapy intervention using Rhythmic Auditory Stimulation was administered for 6 therapy sessions over a period of 3 weeks. Walking ability was measured using the 10 Meter Walk Test to assess the patient’s walking speed before and after the intervention. Results: Showed an improvement in the patient’s walking speed after the Rhythmic Auditory Stimulation intervention. The walking speed increased from 0.75 m/s at the initial evaluation to 1.25 m/s at the final evaluation after 6 therapy sessions. Conclusion: Rhythmic Auditory Stimulation was effective in improving walking speed in elderly post-stroke patients. This intervention can be used as one of the physiotherapy modalities to improve functional walking ability in post-stroke patients.